Effects of a Circuit Training Program on Myokine Levels in Insulin-Resistant Women: A Randomised Controlled Trial - Joanna Karolkiewicz; Monika Krzywicka; Monika Szulińska; Katarzyna Musialik; Dominka Musiałowska; Jacek Zieliński; Agnieszka Bilska; Marzena Ratajczak (Journal of Diabetes Research)
Conclusion: The circuit training program implemented in women newly diagnosed with insulin resistance significantly increased their serum IL-6 and not their IL-10, FGF21, and irisin levels.